On the Processual Nature of Fetal Development: Taking the Subject Out of the Abortion Debate - (:unkn) unknown (My University, 2024)
The abortion debate has perpetually been discussed in terms of when the fetus may gain moral rights (i.e., become a person). Personhood is often discussed in conjunction with when a line should be drawn on the permissibility or impermissibility of termination. This is suggestive of a Substantival framework. Two camps are commonly considered within the metaphysics of pregnancy: the Containment View, where the fetus is viewed as a full person from 16 days, and the Parthood View, where the fetus is viewed similarly to an organ until birth. These views fail to account for the reality of contextual differentiation across pregnancies due to social, environmental, or biomedical factors. The disparity between accounts of the origin of personhood (be it at 16 days or birth) leaves the public mired in disagreement and in a constant battle for reproductive rights. This battle is solvable via a Process Realist Account of Fetal Development, which considers the measurable change and growth that occur in the fetus as the pregnancy progresses. Cases of fetal development are considered to be contextually differentiated, and the practical dependence relation between the pregnant person and the fetus is considered. The date of medical viability, at which the fetus is no longer practically dependent, may then be the cut-off date for abortion. Medical viability differs across countries, however, and each country will have a slightly altered timeline. The Process Realist approach provides a practical benefit to the field via an empirically and epistemically accessible account, wherein only information provided by our natural world is integrated into our problem solving. Medical viability approaches have shown historic success in regard to social, economic, and political rights (Roe v. Wade), and therefore one can expect a Process Realist approach to benefit societies while curtailing harms previously done by the Substance framework.